Acute impact of Hg2+, Cu2+, and Ag+ on the formation of biopolymers and nitrogenous soluble microbiological products in activated sludge for wastewater treatment. (December 2020) - Liu, Tong; Wang, Zi; Wu, Linjie; Guo, Menghan; Yang, Chanyu; Cao, Xin; Qiu, Xiaopeng; Kong, Zan; Zhong, Min; Pan, Baozhu; Ke, Yanchun; Zheng, Xing
Abstract: In the present work, acute impact of heavy metals on activated sludge was investigated, specifically the release of biopolymers and nitrogenous soluble microbiological products (N-SMP) that significantly impact tertiary effluent quality. Based on the previously reported studies, Hg 2+ and Ag + were selected as representative "non-essential" heavy metals, while Cu 2+ was selected as the "essential" heavy metal. Stress tests show that under the present experimental conditions, adding a higher concentration of heavy metals to the activated sludge increases the concentration of biopolymers and SMP in the supernatant; N-SMP increased more significantly than carbonaceous products, implying a greater risk of formation of toxic nitrogenous disinfection by-products or membrane fouling in relevant tertiary treatment processes. The severity of the release of SMP into the supernatant depended on the heavy metal, with an order of Hg 2+ > Ag + > Cu 2+ ("non-essential" > "essential") under identical molar concentrations. The mass balance of typical organics (e.g., biopolymers) in SMP and extracellular polymeric substances (EPS) in activated sludge was analyzed, and a negative correlation between the organics in the SMP and tightly bound EPS was observed, implying that a significant fraction of the SMP could be quickly released from the tightly bound EPS under heavy metal shock conditions and could be related to cell response or damage. Graphical abstract: Image 1 Highlights: Hg2+, Cu2+ & Ag + deteriorate the performance of activated sludge & enzyme activity. In Hg2+, Cu2+ & Ag + shock biopolymers and DON are more released than other organics. Under mass balance condition SMP is negatively related to tightly bound EPS. The correlation of some parameters implies their commonness in chemical property.